Molecular responses to salinity stress in Salix matsudana (Koidz) females and males - Liu, Guoyuan; Wang, Yuqing; Lian, Bolin; Ma, Ziqi; Xiang, Xiaoting; Wu, Jing; Luo, Chunying; Ma, Duojin; Chen, Yanhong; Yu, Chunmei; Zhong, Fei; Wei, Hui; et al. (Frontiers in Plant Science, 2023)
Sexual dimorphism has commonly been found in many species. The phenotypes of Salix matsudana females and males are different under salinity stress. An F1 population was selected to compare the differences between males and females. As a result, males showed stronger roots and heavier dry weights than females. The unique molecular mechanisms of males and females under salinity stress were further analyzed based on the root transcriptome of males and females. Both males and females up-regulated systemic acquired resistance genes, such as ADH and oxygenase-related genes, to resist salt. Moreover, many other abiotic stress response genes were up-regulated in males to adjust to salinity stress, while females showed more down-regulation of nitrogen metabolism-related genes to decrease the harm from salinity stress. The research on salinity tolerance in Salix matsudana males and females would help to further understand sexual dimorphism under selection pressure and provide benefits to the ecological environment.